Hear what I appreciate : activation of consumption motives for healthier food choices across different value segments - Sihvonen, Jenniina; Luomala, Harri (Taylor & Francis, 2017)
This study represents ‘nudging’ interventions aiming to promote healthier food choices by altering the environment where choices are made, without price incentives. The study focuses on the activation of a consumer’s different consumption motives immediately prior to making food choices, thereby drawing a direct goal-priming approach that is postulated to stimulate congruent behaviours. The twofold purpose of this experimental research is to (1) evaluate the usefulness of direct goal priming when aiming at healthier food choices and (2) to identify the boundary conditions that either favour or inhibit the emergence of motivational priming effects. This purpose contributes to the literature on consumer health behaviour in two ways. First, it reveals new motivational origins for health-goal priming effects. Second, it gleans unprecedented empirical evidence for the moderating capacity of consumers’ values. Direct priming of a health goal proved to be effective in steering consumers towards healthier food options. Surprisingly, however, responsibility and status primes also led to an increase in choices of healthy food products. Moreover, a moderation analysis showed that the consumer’s values (achievement, conservation, and universalism) play an important role in how goal priming works. Thus, the success of priming greatly depends on the underlying values of the consumers.
Keywords: health motive; priming; consumer values; food choice; experimental study; consumer behaviour; consumers; choice; food habits; food; consumer research; consumption; marketing; nutritional behaviour; meals; fi=Markkinointi|en=Marketing|